المعادلة الأولى


المعادلة الأولى

 

displaymath26

 

displaymath27

المعادلة الثانية

        5 x - 6 = 3 x - 8                                                                                               

displaymath52

displaymath54

المعادلة الثالثة

displaymath66

displaymath67

displaymath68

displaymath69

displaymath69

displaymath71

 

tex2html_wrap_inline98   =   - 5,25

لمعادلة الرابعة

4x+3x+x = 12-5-9
8x=-2
x=-2%2F8+=+-1%2F4

x=-2%2F8+=+-1%2F4

 

Welcome To My Website
hassan.ab.ma © 2017.Free Web Site